SPARC overexpression inhibits cell proliferation in neuroblastoma and is partly mediated by tumor suppressor protein PTEN and AKT. - Praveen Bhoopathi (Public Library of Science (PLoS), 2012)
Secreted protein acidic and rich in cysteine (SPARC) is also known as BM-40 or Osteonectin, a multi-functional protein modulating cell-cell and cell-matrix interactions. In cancer, SPARC is not only linked with a highly aggressive phenotype, but it also acts as a tumor suppressor. In the present study, we sought to characterize the function of SPARC and its role in sensitizing neuroblastoma cells to radio-therapy. SPARC overexpression in neuroblastoma cells inhibited cell proliferation in vitro. Additionally, SPARC overexpression significantly suppressed the activity of AKT and this suppression was accompanied by an increase in the tumor suppressor protein PTEN both in vitro and in vivo. Restoration of neuroblastoma cell radio-sensitivity was achieved by overexpression of SPARC in neuroblastoma cells in vitro and in vivo. To confirm the role of the AKT in proliferation inhibited by SPARC overexpression, we transfected neuroblastoma cells with a plasmid vector carrying myr-AKT. Myr-AKT overexpression reversed SPARC-mediated PTEN and increased proliferation of neuroblastoma cells in vitro. PTEN overexpression in parallel with SPARC siRNA resulted in decreased AKT phosphorylation and proliferation in vitro. Taken together, these results establish SPARC as an effector of AKT-PTEN-mediated inhibition of proliferation in neuroblastoma in vitro and in vivo.